1982
DOI: 10.1084/jem.156.4.1235
|View full text |Cite
|
Sign up to set email alerts
|

Activation of complement by serum-resistant Neisseria gonorrhoeae. Assembly of the membrane attack complex without subsequent cell death.

Abstract: Interaction of the human complement system in normal human serum (NHS) with serum-resistant and -sensitive Neisseria gonorrhoeae was evaluated to better understand the mechanism of serum-resistance. Complement activity (CH50) was depleted from NHS in a dose-dependent fashion by both serum-resistant and -sensitive N. gonorrhoeae. No detectable CH50 remained in NHS incubated with 10(9) colony-forming units (CFU)/ml serum of either resistant or sensitive strains. When smaller numbers of bacteria were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Alternatively, the capsule may preclude covalent attachment of C3 to the bacterial surface which would not permit amplification by the alternative pathway (33). In any event, the mechanism ofserum-resistance of encapsulated C. fetus appears to be novel and differs from those described for smooth Enterobacteriaceae (15), or serum-resistant gonococci (34,35). For those organisms, C3 binding and C5b-9 generation are efficient, but for a variety of reasons (18, 34) the terminal membrane attack complex fails to insert into vital cell membrane structures.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the capsule may preclude covalent attachment of C3 to the bacterial surface which would not permit amplification by the alternative pathway (33). In any event, the mechanism ofserum-resistance of encapsulated C. fetus appears to be novel and differs from those described for smooth Enterobacteriaceae (15), or serum-resistant gonococci (34,35). For those organisms, C3 binding and C5b-9 generation are efficient, but for a variety of reasons (18, 34) the terminal membrane attack complex fails to insert into vital cell membrane structures.…”
Section: Resultsmentioning
confidence: 99%
“…MACs (or C5b-9) form on the surfaces of both serumsensitive and serum-resistant organisms (22,27). Both sensitive and resistant strains consume equivalent amounts of C9 and bind similar numbers of C7 and C9 molecules when incubated in NHS (22,27).…”
Section: Activation and Disposition Of Complementmentioning
confidence: 99%
“…In addition, (iii) blocking antibodies, directed at outer membrane protein antigens, modulate or down-regulate bacterial killing, mainly by preventing binding of bactericidal antibodies to lytic epitopes (26,49). Finally, and least well understood, (iv) there is a partial failure to form the C5 convertase necessary for full development of membrane attack complexes (MACs or C5b-9 [11, 12]) but also a failure of MACs that do form to fully insert through the gonococcal outer membrane (22,27). In addition, less C3 may bind to serum-resistant organisms, and C3 that does bind may not be hemolytically active (51).…”
mentioning
confidence: 99%
“…Stable binding of the MAC to the bacterial membrane without lysis or death has been reported with certain serum-resistant strains of Neisseria gonorrhoeae (39,48,49). Joiner et al (39) found evidence that nonbactericidal C5b-9 was associated with bacterial outer membrane constituents, was trypsin sensitive, and ran on sucrose density gradients as complexes of higher molecular weight than did the bactericidal MAC formed on the serum sensitive strain.…”
Section: Discussionmentioning
confidence: 99%
“…5 A) most likely represents terminal C5b-9 complexes containing multiple molecules of C9, since at least three molecules of C9 are necessary for formation of SDS-resistant tubular polyC9 (50). High molecular weight MACs are generally heterogenous, containing both SDS-resistant tubular polyC9 and linear C9 that is broken down to monomeric C9 by SDS under reducing conditions (49); both populations are seen in the SDS-PAGE of peak A (Fig. 6, lane 1).…”
Section: Resultsmentioning
confidence: 99%